Evaluation of Fetal Cardiac Output and Modified Myocardial Performance Index in Pregnant Women with Idiopathic Polyhydramnios: A Case Control Study from a Tertiary Hospital - Sakcak, Bedri; Denizli, Ramazan; Farisoğulları, Nihat; Haksever, Murat; Turgut, Ezgi; Kara, Ozgur; Tanacan, Atakan; Sahin, Dilek (Zeitschrift für Geburtshilfe und Neonatologie, 2023)
Purpose This study aimed to investigate fetal cardiac output and myocardial performance index in pregnant women with idiopathic polyhydramnios and compare them to healthy pregnant women.Methods Thirty patients admitted to Ankara City Hospital at 24–39 weeks of gestation with idiopathic polyhydramnios were included as the study group. Clinical characteristics, fetal cardiac output, and fetal modified myocardial performance index (Mod-MPI) were compared between the groups.Results The combined cardiac output (CCO), left cardiac output (LCO), right cardiac output (RCO), pulmonary artery velocity time integral (PA-VTI), and aortic VTI were statistically significantly higher in the study group (p=0.003, p=0.028, p=0.002, p=0.000, and p=0.017, respectively).The idiopathic polyhydramnios group had a significantly higher Mod-MPI and isovolumetric contraction time (ICT) and a significantly lower ejection time (ET) compared to the controls (p=000, p=0.003, and p=0.023, respectively). In the idiopathic polyhydramnios group, the aortic max (p=0.009) and aortic VTI (p=0.047) values were significantly lower and the left ventricular outflow tract isovolumetric relaxation time (LVOT-IRT) (p=0.021) was significantly higher in cases where the NICU was required. According to the ROC analysis performed in the idiopathic polyhydramnios group, the optimal cut-off values of aortic max, aortic VTI, and LVOT-IRT in the prediction of the NICU requirement were (57.5, 0.089 and 41.5, respective cut-off value) (p=0.010, p=0.048, p=0.021, respectively).Conclusions Both fetal cardiac output and Mod-MPI values were altered in fetuses with idiopathic polyhydramnios.
Keywords: idiopathic polyhydramnios; fetal cardiac output; myocardial performance index; perinatal outcomes